YAATRIASSIST : Passenger Facilitation Using AI and ML - Nihalchandani, Ankit Dilip; Kulshrestha, Shivang Deepak; Lakhani, Raj Kirit; Pandagre, Deepak; Adhvaryu, Rachit (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
YaatriAssist is a revolutionary travel application that reimagines global adventures with unmatched convenience and sophistication. This innovative app integrates essential functionalities seamlessly, offering real-time GPS navigation for confident exploration and integrated weather updates for preparedness in diverse climates. It features a comprehensive travel log for capturing and cherishing memories, along with an optimized scheduler to maximize trip enjoyment. The curated news hub keeps travelers informed about local events and global developments, while Travel mate fosters connections between fellow explorers, enhancing journey richness. Language barriers are effortlessly overcome with translation and OCR functionalities. Customizable settings ensure personalized experiences, evolving with individual travel needs. Facilitating bookings for flights, accommodations, and activities directly through the app streamlines trip management, offering unparalleled convenience. In summary, YaatriAssist stands as the epitome of travel convenience, catering to both seasoned globetrotters and business travelers, empowering users to navigate, explore, and engage with the world confidently and effortlessly.
Keywords: YaatriAssist; Travel Application; Global Adventures; Artificial Intelligent; Machine Learning.